Strategic Collaboration Between Local Government and DPRD in The Implementation of Regional Autonomy - Marthina Raga Lay (International Journal Labs, 2024)
In an effort to realize the goals of regional autonomy, strategic collaboration between the Regional Government and the DPRD must be able to be mobilized synergistically. Local Government and DPRD are equal partners in the administration of local government. Both agencies exist with their respective duties and functions. With their respective functions, the two institutions are expected to be able to build a working relationship that is enabling (enabling), and is not a competitor with each other in carrying out their duties and functions. Listening to the pattern of local government administration that has been existing so far, it seems that the implementation of decentralization requires new innovations in the field of governance. Thus, the way or method of revitalization offered, it is hoped that the working relationship between the regional government and the DPRD has strong pillars so that the journey of regional autonomy can achieve the goals set.